Communication in the Ukrainian Korovay Rite - Serko, Olena (Tautosakos darbai, 2020)
In the rites, ritual sphere, and worldview of the Ukrainian people, the idea of exalting bread takes on a special significance. Bread acquires its greatest symbolism in wedding ceremonies, where it was called a korovay, and personified the birth of a new family, procreation, welfare, and prosperity.The article is devoted to the study of the korovay rite as performed in the village of Klintsy, Dubno district, Rivne region. The author explores the communicative specificity of the korovay rite as a symbolic form of social interaction. The focus is on determining the participants in the ritual action, their role and functions, and also emphasizes the special importance of the musical component, which is the leading means of communication in the rite. I also review some key approaches to the study of ritual phenomena, as exemplified in the korovay rite, and communication (ritual, musical, interpersonal, group, sacred, auto-communication), both as individual and as interrelated subjects. The study reveals the importance of the korovay rite in modern Ukrainian society, showing how it ensures communication between generations through the transmission of important sociocultural meanings.
Keywords: rite; korovay rite; communication; Ukrainian folklore; folk traditions